IMPROVEMENT OF THE GRATE GRID OF THE 1VP FIBER PURIFIER - I.A. Nishonov (Western European Studies, 2024)
This article investigates the recent advancements in the design and performance of the grate grid in the 1VP fiber purifier. The grate grid plays a pivotal role in the fiber purification process, directly influencing the efficiency and quality of the output. The study details the modifications implemented to enhance the grate grid's functionality, focusing on innovative engineering approaches and the use of advanced materials. These improvements aim to increase operational efficiency, extend the equipment's lifespan, and reduce maintenance requirements. The results highlight substantial gains in the performance and reliability of the 1VP fiber purifier, providing valuable insights for optimizing similar purification systems in the industry. To achieve cleaning efficiency by replacing the column grid of the 1VP type fiber cleaner used in cotton cleaning enterprises with a trapezoidal column.
Keywords: 1VP; grate grid; cleaning